Is extraction bad? : encomienda and development in Colombia since 1560 (2017)
We explore the impact of encomienda, a forced-labor institution imposed by the Spanish throughout Latin America during three centuries, on long-term development outcomes in Colombia. Despite being a classically extractive institution, municipalities that had encomiendas in 1560 have higher development indicators than otherwise-similar, neighboring municipalities without. Encomienda is associated with higher municipal GDP/capita, lower poverty and infant mortality, and higher secondary school enrolments today. Further probing implies a mechanism by which encomenderos founded the local state in the colonial territories they dominated.  This stronger local state persisted through Colombia's war of independence and the chronic instability of the early republic. It mobilized resources and invested in public goods in ways that initially suited encomenderos, but over long periods of time also spurred economic and human development.  Our results highlight the benefits of disaggregating "institutions" to analytically discrete components, and of pushing analysis to the subnational level.